DFT Investigation of the Molecular Properties of the Dimethylglyoximato Complexes [M(Hdmg)2] (M = Ni, Pd, Pt) - Niazi, Maryam; Klein, Axel (Inorganics, 2021)
Important applications of the NiII, PdII and PtII complexes [M(Hdmg)2] (H2dmg = dimethylglyoxime) stem from their metal...metal stacked virtually insoluble aggregates. Given the virtual insolubility of the materials, we postulated that the rare reports on dissolved species in solution do not represent monomolecular species but oligomers. We thus studied the structural and spectral properties of the monomolecular entities of these compounds using density functional theory (DFT) and time-dependent DFT computations in dimethyl sulfoxide (DMSO) as a solvent. The molecular geometries, IR and UV-vis spectra, and frontier orbitals properties were computed using LANL2DZ ecp and def2TZVP as basis sets and M06-2X as the functional. The results are compared with the available experimental and other calculated data. The optimised molecular geometries proved the asymmetric character of the two formed O–H…O bonds which connect the two Hdmg‒ ligands in the completely planar molecules. Calculated UV-vis spectra revealed the presence of three absorptions in the range 180 to 350 nm that are red-shifted along the series Ni–Pd–Pt. They were assigned to essentially ligand-centred π−π* transitions in part with metal(d) to ligand(π*) charge transfer (MLCT) contributions. The notorious d‒p transitions dominating the colour and electronics of the compounds in the solid-state and oligomeric stacks are negligible in our monomolecular models strongly supporting the idea that the previously reported spectroscopic observations or biological effects in solutions are not due to monomolecular complexes but rather to oligomeric dissolved species.